Physical type of the Armenian Highlands populations in antiquity (based on osteometrical materials from urban and rural settlements) - Khudaverdyan A.Yu. (Вестник археологии, антропологии и этнографии, 2021)
The paper is concerned with the analysis of osteometrical data from the antique populations of the Armenian Highlands, i.e. anthropological materials of burials dated to the 1st–3rd c. AD. We analyse the differences in an-thropological characteristics between urban and rural population of Armenia in antiquity. In total, 78 individuals of both sexes have been examined using traditional osteological methods. The study involved visual examination of the skeletons, images, descriptions and radiography. For the intergroup comparison, canonical analysis based on the averaged intergroup correlation matrix was used [Deryabin, 1983]. Visually, bones of the villagers appear to be more massive and quite elevated. Men, buried in rural areas differ from those from urban environments in smaller longitudinal dimensions of humerus, radius and ulna, and in larger icircumference of humerus, ulna and femur. Analysis of the data shows that the studied groups carry some features characteristic for populations adapted to high-altitude environments. Intergroup analysis suggests that the closest to the urban male groups would be the Maeotian population from the eastern coast of the Sea of Azov. The female part of the urban com-munity is close to the population of the first centuries AD from Gurmiron. Male villagers show similar features to those of Scythians of Ukraine (Scythian Neapolis); villagers are morphologically close to groups of Sarmatian cultures of the Lower Volga Region. Indirectly, this observation confirms the fact of stable, continuous migration flow into the territory of the Armenian Highlands. There is a certain agreement in the differentiation pattern of the ancient Armenian Highland population from the osteometric and craniometrics data. The osteometric data can be a rather important source of information for reconstruction of biological affinities of human populations.